(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2025)
Using an acetic acid leaching process to extract calcium components from converter steel slag, evaporation, and crystallization to obtain high-purity CaO material. The influence of leaching parameters on the CaO content of the material was investigated. The shrinking core model was applied to analyze the leaching rate in a weakly acidic solution. Finally, the CO2 adsorption performance of the CaO material under different adsorption conditions was evaluated, and the adsorption process and reaction mechanism were investigated using XRD and SEM analysis. The results showed that leaching temperature and acetic acid concentration significantly impacted the CaO content. The optimal leaching parameters were found to be an acid concentration of 1 M, a solid-to-liquid ratio of 1:10, a leaching temperature of 70 °C, and a duration of 2 h, under which the CaO content reached a maximum of 86.3%. Kinetic results indicated that stirring shifted the rate-controlling step of calcium leaching from external diffusion and surface chemical reactions to internal diffusion. In the temperature range of 40-70 °C, the rate-controlling step was governed by internal diffusion. XRD and SEM results confirmed the high purity of the CaO material. CaO first transformed into Ca(OH)2, which adsorbed CO2 to form CaCO3. The deposition of CaCO3 on the material surface hindered the contact between Ca(OH)2 and CO2, reducing carbon adsorption efficiency. Increasing the CaO content enhanced adsorption performance significantly. In the adsorption temperature range of 0-100 °C, ensuring effective contact between Ca(OH)2 and CO2 was crucial. The calculated CO2 capture capacities at 30 °C, 50 °C, and 70 °C were 0.32 g/g, 0.24 g/g, and 0.17 g/g, respectively. This study can provide a reference for the high-value utilization of steel slag and the reduction of CO2 emission in iron and steel enterprises.